Post-remediation use of macrophytes as composting materials for sustainable management of a sanitary landfill. Issue 4 (3rd April 2017) - Song, Uhram
ABSTRACT: To increase the remediation ability and life expectancy of a leachate channel in a sanitary landfill, the plants used for remediation were composted as a post-remediation management technique. Phragmites australis or Typha angustifolia used for phytoremediation in a landfill leachate channel was harvested and used as a co-composting material with sewage sludge. The macrophyte compost was applied to the slope of a landfill on which plants were introduced for revegetation and to plants grown in pots to test for acute effects of the compost. The compost of the macrophytes successfully increased soil moisture and nutrient contents both on the landfill slope and in the soil of the pot experiment. Additionally, the rates of photosynthesis and the nutrient contents increased for plants grown in macrophyte compost. Thus, the revegetation or restoration management of the landfill would improve with the macrophyte compost used as a soil conditioner. The harvest of the macrophytes has the additional benefit of improving the remediation function of the leachate channel. Therefore, to sustainably manage both the leachate channel and the landfill, the composting of post-remediation macrophytes is an environmentally friendly and economically affordable method.